PENGEMASAN MATERI PEMBELAJARAN TARI WIRA PERTIWI BERBASIS POWERPOINT STAND ALONE UNTUK SEKOLAH MENENGAH ATAS - Khoiriyah Nasution (Universitas Negeri Medan, 2020)
ABSTRACT This study aims to package the Wira Pertiwi Dance learning according to KD 3.1 in the Stand Alone Powerpoint learning media for high school class XI students. The theoretical basis used as a guideline in this study is the theory of Wina (2011: 20) along with Rudi Susilana and Cepi Riyana (2017: 102) which explain how the stages or procedures are in making Stand Alone Powerpoint. The technique of collecting data was carried out by means of observation, interviews, literature study and documentation. The packaging method uses computer laboratory work. The research method used is descriptive qualitative in which the data obtained are then processed and analyzed carefully. The results of data processing are arranged systematically in the form of a thesis. The research process or packaging method is carried out in four stages, namely: the first stage of program identification, namely ensuring the correct program selected, the program used by Powerpoint. The second stage was collecting supporting materials such as material, photos, sound and video of the Wira Pertiwi Dance. The third stage is the process of working on learning media according to the material that has been collected. The final stage is a program review by conducting a material feasibility test and a media feasibility test, revising it, then making it ready for use. This product obtained the results of the feasibility test with a score of 94% by material experts and the results of the due diligence with a score of 91.1% by media experts. The overall result of the feasibility test got a score of 92.5%. Thus, the results of research on the packaging of Wira Pertiwi Dance learning in Stand Alone Powerpoint learning media include material understanding concepts, techniques, and procedures for senior high school class XI students in Medan. Keywords: Packaging, Wira Pertiwi Dance, Stand Alone Powerpoint. ABSTRAKPenelitian ini bertujuan mengemas pembelajaran Tari Wira Pertiwi sesuai KD 3.1 memahami konsep, teknik dan prosedur dalam meniru ragam gerak tari kreasi, dalam media pembelajaran Powerpoint Stand Alone untuk siswa kelas XI Sekolah Menengah Atas. Landasan teori yang dijadikan pedoman pada penelitian ini adalah teori Wina (2011:20) beserta Rudi Susilana dan Cepi Riyana (2017:102) yang menjelaskan bagaimana tahapan atau prosedur dalam pembuatan Powerpoint Stand Alone. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, studi kepustakaan dan dokumentasi. Metode pengemasan menggunakan kerja laboratorium komputer. Metode penelitian yang digunakan yakni deskriptif kualitatif di mana data yang diperoleh kemudian diolah dan dianalisis dengan teliti. Hasil pengolahan data disusun secara sistematis dalam bentuk skripsi. Proses penelitian atau metode pengemasan dilakukan dalam empat tahapan yakni : tahapan pertama identifikasi program yaitu memastikan program yang dipilih sudah tepat, program yang digunakan Powerpoint. Tahapan kedua mengumpulkan bahan pendukung seperti materi, foto, suara dan juga video Tari Wira Pertiwi. Tahap ketiga proses pengerjaan media pembelajaran sesuai materi yang sudah dikumpulkan. Tahap terakhir Review program dengan dilakukannya uji kelayakan materi dan uji kelayakan media, revisi, kemudian siap digunakan. Produk ini memperoleh hasil uji kelayakan dengan skor 94% oleh ahli materi dan hasil uji kelayakan dengan skor 91,1% oleh ahli media. Hasil keseluruhan uji kelayakan mendapatkan skor 92,5%. Dengan demikian, hasil penelitian pengemasan pembelajaran Tari Wira Pertiwi dalam media pembelajaran Powerpoint Stand Alone meliputi materi memahami konsep, teknik, dan prosedur untuk siswa kelas XI Sekolah Menengah Atas di Medan sangat layak digunakan. Kata Kunci: Pengemasan, Tari Wira Pertiwi, Powerpoint Stand Alone.